NOBILITY OF WATER IN VEDIC TRADITION - Madhusudan Das; Gourango Biswas (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Hinduism is one of the oldest religions in the world. And the people of the Hindu religion take refuge in some belief or entity and proceed on the path of eternity. They believe bathing in this holy water removes all the impurities from the heart. Holy water itself awakens self-consciousness. The question arises, how the existence of water has been recognized in Vedic literature? It says that water existed before creation. But this vow is not possible without water. Only water can elevate them to godhood. Water is the only source of all desires. Adhvaryu sprinkles water from his kamaṇḍalu to ward off those who disturb the sacrifice or the enemies. The contribution of water in purification or sanctification is undoubtedly undeniable. Vedic sages are also full of praise for water. He described the water as healthy, pure and pleasant. And it has more healing properties than the food-giving mother. And productive of immovable and movable nature etc. sIt is through this affection that divinity is revealed in the hearts of human beings. Śānti water is used even for barren women to give birth to children. Motherly water destroys unconsciousness and purifies. Water is purified through mantra. This water moistens the land, gives medicinal fertility, and nourishes the plants, making it fit for consumption. However, different types of water irrigation are described in different Vedas. Moreover, regarding water conservation, it is said in Yajurveda that water should never be polluted- mā’po mauṣadhīrhiṁsī rdhāmno rājãstato varuṇa no muñca/ There is also praise for not cutting down trees to protect water or water bodies. The contribution of holy water from Bhūmiṣhta to Śrādhānuṣṭhāna is unimaginable. So all this water is considered to protect oneself from sin. So we cannot think of the origin of anything without water.